2020
DOI: 10.1177/0363546520975435
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Platelet-Rich Plasma Leukocyte Concentration on Arthroscopic Rotator Cuff Repair: A Network Meta-analysis of Randomized Controlled Trials

Abstract: Background: It is unclear whether leukocyte-poor (LP) or leukocyte-rich (LR) varieties of platelet-rich plasma (PRP) as an adjuvant to arthroscopic rotator cuff repair (ARCR) result in improved tendon healing rates. Purpose: To perform a network meta-analysis of the randomized controlled trials in the literature to ascertain whether there is evidence to support the use of LP- or LR-PRP as an adjunct to ARCR. Methods: The literature search was based on the PRISMA (Preferred Reporting Items for Systematic Review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 47 publications
1
34
0
1
Order By: Relevance
“…A 2020 meta-analysis of 13 RCTs compared the effect of arthroscopic rotator cuff repair with either LR-or LP-PRP on rates of retear, healing, and pain scores. 38 LP-PRP reduced rates of retear and/or incomplete tendon healing after fixation for both small and medium to large tears. In addition, patients with this treatment experienced reduced pain, as measured by multiple pain scales.…”
Section: Rotator Cuff Tendinopathymentioning
confidence: 90%
See 1 more Smart Citation
“…A 2020 meta-analysis of 13 RCTs compared the effect of arthroscopic rotator cuff repair with either LR-or LP-PRP on rates of retear, healing, and pain scores. 38 LP-PRP reduced rates of retear and/or incomplete tendon healing after fixation for both small and medium to large tears. In addition, patients with this treatment experienced reduced pain, as measured by multiple pain scales.…”
Section: Rotator Cuff Tendinopathymentioning
confidence: 90%
“…However, post hoc analyses showed that LR-PRP did not lead to significant improvements over the control group with respect to any outcome metric. 38 Durability of therapeutic benefit is not well characterized, with some studies showing lower rates of re-tears at 1 year. [39][40][41] Others suggest that improvements in pain and functionality wane after 1 year.…”
Section: Rotator Cuff Tendinopathymentioning
confidence: 99%
“…However, although LR-PRP appeared to be better than the control, the results were not statistically significant. 14 Furthermore, LR-PRP was not significantly inferior to LP-PRP, and a difference could not be determined. 14 Randelli et al 1 found that PRP made an early impact on tendon healing and pain, but this did not translate to longterm improvements.…”
mentioning
confidence: 92%
“…14 Furthermore, LR-PRP was not significantly inferior to LP-PRP, and a difference could not be determined. 14 Randelli et al 1 found that PRP made an early impact on tendon healing and pain, but this did not translate to longterm improvements. PRP likely is absorbed in the early postoperative healing phase and does not stay in the joint long term; thus its long-term effects are questionable.…”
mentioning
confidence: 92%
See 1 more Smart Citation